A unification procedure to the analysis and synthesis of antenna arrays - Casimiro, A. M. E. S. (2019)
The far ﬁeld pattern synthesis of arrays involves the calculation of an antenna array excitation factor, and this is performed in diﬀerent ways depending on the adopted method. On the other hand, the determination of the array factor, when the excitation coeﬃcients are known, is usually performed by a direct summation. This paper proposes a generalized procedure that can be applied to the analysis and to the synthesis of continuous and discrete arrays to evaluate the far ﬁeld pattern. The proposed method employs the Fourier Relation, to derive the relationship between the array factor and the excitation distribution of a discrete array, and it is based on the Fourier Transform. Due to the ﬁnite nature of arrays, it is possible to use the Fast Fourier Transform, which permits an eﬃcient and rapid way to perform the calculations using a computer. The method is applied to some typical synthesis problems and compared with published results. It can be seen that this new theory simpliﬁes the usual synthesis procedure and that the processing time is dramatically reduced. Then, the method is applied to obtain synthesis techniques that control the radiation pattern through the use of the Fourier Transform properties.